Taking a moral holiday? Physicians’ practical identities at the margins of professional ethics - Gils-Schmidt, Henk Jasper van (Journal of medical ethics, 2024)
Physicians frequently encounter situations in which their professional practice is intermingled with moral affordances stemming from other domains of the physician’s lifeworld, such as family and friends, or from general morality pertaining to all humans. This article offers a typology of moral conflicts ‘at the margins of professionalism’ as well as a new theoretical framework for dealing with them. We start out by arguing that established theories of professional ethics do not offer sufficient guidance in situations where professional ethics overlaps with moral duties of other origins. Therefore, we introduce the moral theory developed by Christine M. Korsgaard, that centres around the concept of practical identity. We show how Korsgaard’s account offers a framework for interpreting different types of moral conflicts ‘at the margins of professionalism’ to provide either orientation for solving the conflict or an explanation for the emotional and moral burden involved in moral dilemmas.